Proceso de extracción de bioactivos de plantas en dos especies vegetales (Thymus Vulgaris L., Mentha Piperita) para caracterización con espectrometría óptica. - Yánez Zapata, Alex Vinicio (2023)
This research is a sequence of three projects previously carried out at the Technical University of Cotopaxi 2021-2022, where possible studies of astronomical and meteorological factors related to the influence on plant phenology are identified through a bibliographic review. From the above mentioned, some bioactives were determined to study the proposed relationships. The bibliographical analysis and the bioactives of the previous projects were taken into account to continue with the subsequent investigation. The work aims to develop a process for extracting bioactive from plants in two plant species, thyme and peppermint, for characterization with optical spectrometry where the two species were conditioned under field conditions Urcuqui, Imbabura, to later select samples of plant material for analysis of bioactive. In addition, to test bioactive extraction methods using the simple technique (procedure one) and cell disruption called bath sonicator and tip sonicator (corresponding to procedures two and three) for UV-VIS and RAMAN optical spectrometry evaluation. The research was carried out at Yachay Tech University. In conclusion, it was possible to obtain concentrations of bioactive, procedure three being the most optimal with conditions: cell disruptor for 5 minutes in tip sonicator. This methodology is proposed since it has been adjusted to its conditions and identifies the available instruments. This project represents a first step for identification of bioactives by optical spectrometry in the determined species, in order to study their spectra in different laboratory and field conditions in the future.